2017
DOI: 10.2174/1871527315666160902144513
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses Tumor Growth and Angiogenesis in Human Glioma Cells Through Modulation of Vascular Endothelial Growth Factor/ Angiopoietin-2/Thrombospondin-1 Signaling

Abstract: This study shows that curcumin inhibits tumor growth by inhibiting VEGF/Ang-2/TSP-1- mediated angiogenesis in a xenograft glioma mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Several of these compounds were previously shown to exert antitumor effects. For example, curcumin (M02 in Table 1 ) is widely used against tumors and suppresses the growth of gastric tumor cells [ 17 ] and human glioma cells [ 18 ]. Similarly, curcumol (M01) induces apoptosis in SPC-A-1 human lung adenocarcinoma cells [ 19 ], hederagenin (M06) exerts cytotoxicity in human breast and lung cancer cells [ 20 ], and demethoxycurcumin (M10) inhibits the growth of human epithelia ovarian cancer cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several of these compounds were previously shown to exert antitumor effects. For example, curcumin (M02 in Table 1 ) is widely used against tumors and suppresses the growth of gastric tumor cells [ 17 ] and human glioma cells [ 18 ]. Similarly, curcumol (M01) induces apoptosis in SPC-A-1 human lung adenocarcinoma cells [ 19 ], hederagenin (M06) exerts cytotoxicity in human breast and lung cancer cells [ 20 ], and demethoxycurcumin (M10) inhibits the growth of human epithelia ovarian cancer cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, their function can be significantly repressed by curcumin, and more effectively repressed by curcumin in combination with flavonoids, such as EGCG [185]. Such applications can lead to repression of angiogenesis via decreased VEGF production [186][187][188], blocking monocyte binding via downregulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-KB) signalling [189]. A model of the therapeutic effects of curcumin and flavonoids on the tumour microenvironment and tumour development is shown in Figure 2.…”
Section: Effects Of Curcumin and Flavonoids On Tumour-associated And -Infiltrating Cells: Suppression Of Ctc Supportmentioning
confidence: 99%
“…Figure 2. Simplified model of curcumin and flavonoids effects on the NSCLC microenvironment[83,119,148,158,159,162,168,170,174,175,[186][187][188][189][190][191][192][193][194][195][196]. A necessary part of igenesis and CTC spreading is the interaction of NSCLC cells with tumour-associated cells.…”
mentioning
confidence: 99%
“…Several studies have shown the effects and mechanisms of CCM against human neuroglioma cells (19)(20)(21). CCM was shown to induce G2/M cell cycle arrest and apoptosis in U87 cells by increasing forkhead box protein O1 expression (22), and was also reported to suppress tumor growth and angiogenesis in human glioma cells through modulation of VEGF/angiopoietin-2/thrombospondin-1 signaling (23,24). Since inflammatory factors can enhance glioma growth, and CCM is an effective anti-inflammatory factor, it remains unknown whether CCM can exert its antitumor effects by inhibiting the inflammatory HSP60/TLR-4 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%